Intellectus Amoris, Liberationi: From Jon Sobrino’s reconceptualization of theology to tripartite diaconal action research (Nordic Journal of Practical Theology, 2020)
This article revisits liberation theologian Jon Sobrino’s suggestive reconceptualization of theology and theological method as ‘intellectus amoris’, and as a practical and liberative ‘mystagogy’. Sobrino’s theological approach is held together with the recent renewal of action research in search for animprovement of the current models and methods of diaconal research, making it not only research ‘on’ diaconal practice, but furthermore, or rather, research ‘as’ diaconia, i.e. research or systematic and transformative processes of learning from within diaconal practices. This way, the potentially diaconal character of action research itself can come to the fore.